Kulcs egy alternatív mikrofinanszírozási modell sikeréhez - Balogh, László; Gál, Veronika Alexandra; Parádi-Dolgos, Anett; Sipiczki, Zoltán (Acta Scientiarum Socialium, 2013)
Key to the success of an alternative microfinance model The social and economic conditions and trends of the 20th century increasingly focus on new alternative financial solutions beside the traditional bank systems – complementing its shortcomings. The movement – fighting against extreme poverty – was launched from India by the Grameen Bank. The bank of the poor model is providing financial assistance for starting up micro-enterprises. In addition there is an educational technology in it; its aims are the staying on feet, the improvement of living conditions and the development of personality by involving people in economic processes. Many countries of the World has successfully adopted this model, but in our country the initiatives served marginal results. Our aim is to examine the efficiency and effectiveness of the Hungarian prac-tice. We explore the external and internal, social and economical factors affecting the function of programs. We outline the main dilemmas of Hungarian poor banking model and record the success criteria from a methodological point of view.
Keywords: Grameen model; dilemmas of adaptation; government's role; mentors; credit conditions